The potential of rice bran (Oryza sativa) nutritional components as a functional food for healthy consumption: A review - A. N. Agustina; A. N. M. Ansori; R. Puspita; M. Citrawati; S. Wahyuningsih; S. Tuba; M. A. Herdiansyah; M. Kristanti (Пищевые системы, 2025)
Indonesia produced 56.54 million tons of paddy (Oryza sativa) dried grain in 2018, with rising demand leading to increased production of by-products such as rice bran. Rice bran, a nutrient-rich by-product, contains high levels of dietary fiber and bioactive compounds with notable anti-cholesterol and anti-diabetic properties. Numerous in vitro and in vivo studies highlight the antioxidant capabilities of rice bran, mainly due to tocopherol, γ-oryzanol, and β-carotene, which function as primary and secondary antioxidants. Effective extraction and fractionation techniques can isolate these antioxidants from rice bran. Cultivation practices significantly impact the nutritional composition of rice bran. The nitrate reductase enzyme (NRA) test can assess growth conditions, which may reflect metabolic activity in paddy plants. Enhanced dietary fiber components (hemicellulose, cellulose, and lignin) and niacin levels make rice bran a promising alternative nutrient source in Indonesia, where unhealthy lifestyles are prevalent. With Indonesia’s significant rice production and bran demand, processed rice bran products hold substantial potential as functional foods for routine consumption, promoting a healthier diet and aiding in prevention of degenerative diseases.